METAFORA DALAM LIRIK LAGU BAHASA JEPANG KARYA KENSHI YONEZU - Rodiyanti, Puput; Hermandra, Hermandra; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the forms and meanings of metaphors contained in the Japanese song lyrics in Kenshi Yonezu's album "Stray Sheep". This study aims to identify the form of metaphors and analyze the meaning in the lyrics of the song by Kenshi Yonezu on the album "Stray Sheep". The method used in this research is descriptive qualitative. The source of the data in this research is the lyrics of Japanese songs by Kenshi Yonezu. The data found in this study is conceptual metaphor and ontological metaphor. The results of this study are 14 data and analysis of meaning related to the type of metaphors. In this study, the least data found is the type of ontological mataphor, this is indicated by 6 data found in the results of this study. While the most commonly found is the type of conceptual metaphor marked by the presence of 8 data found in the results of this study.Key Words: Metaphors, Kenshi Yonezu